Cosmic strings-induced CMB anisotropies in light of weighted morphology - Afzal, Adeela; Alakhras, M; Kanafi, M H Jalali; Movahed, S M S (Monthly notices of the Royal Astronomical Society, 2025)
ABSTRACT Motivated by the morphological measures in assessing the geometrical and topological properties of a generic cosmological stochastic field, we propose an extension of the weighted morphological measures, specifically the nth conditional moments of derivative (cmd-n). This criterion assigns a distinct weight to each excursion set point based on the associated field. We apply the cmd-n on the cosmic microwave background (CMB) to identify the cosmic string networks (CSs) through their unique Gott–Kaiser–Stebbins effect on the temperature anisotropies. We also formulate the perturbative expansion of cmd-n for the weak non-Gaussian regime up to $\mathcal {O}(σ _0^3)$. We propose a comprehensive pipeline designed to analyse the morphological properties of string-induced CMB maps within the flat sky approximation. To evaluate the robustness of our proposed criteria, we employ string-induced high-resolution flat-sky CMB simulated patches of 7.2 deg$^2$ size with a resolution of 0.42 arcmin. Our results demonstrate that the minimum detectable value of cosmic string tension is $Gμ \gtrsim 1.9× 10^{-7}$ when a noise-free map is analysed with normalized cmd-n. Although for the ACT, CMB-S4, and Planck-like experiments at 95.45 per cent confidence level, the normalized cmd-n can distinguish the CSs network for $Gμ \gtrsim 2.9 × 10^{-7}$, $Gμ \gtrsim 2.4× 10^{-7}$, and $Gμ \gtrsim 5.8× 10^{-7}$, respectively. The normalized cmd-n exhibits a significantly enhanced capability in detecting CSs relative to the Minkowski Functionals.